Antioxidant-rich Clove Extract, A Strong Antimicrobial Agent Against Urinary Tract Infections-causing Bacteria in vitro - Vanessa Lee Rosarior; Pei Shan Lim; Wei Kit Wong; Chen Son Yue; Hok Chai Yam; Sheri-Ann Tan (Tropical Life Sciences Research, 2021)
Clove (Syzygium aromaticum) is an exotic culinary spice that has been used for centuries due to its known antimicrobial and antioxidant properties. The main aim of this study is to compare the antimicrobial activity and antioxidant capacity of clove ethanolic extract (CEE) and commercial clove essential oil (CEO) at a standardised eugenol content. Disk diffusion assay showed that CEE (2000 ?g) was able to exhibit broad-spectrum inhibition against both Gram negative and Gram positive Urinary Tract Infections (UTIs)-causing pathogens: Proteus mirabilis (19.7 ± 0.6 mm) > Staphylococcus epidermidis (18 mm) > Staphylococcus aureus (14.7 ± 0.6 mm) > Escherichia coli (12.7 ± 0.6 mm) > Klebsiella pneumoniae (12.3 ± 0.6 mm) (according to the size of inhibition zone). Interestingly, the comparison between CEE and commercial CEO revealed that the former demonstrated stronger antimicrobial and antioxidative properties at similar eugenol concentration. The EC50 of DPPH (1,1-diphenyl-2-picrylhydrazyl), ABTS (2,2’-azino-bis(3-ethylbenzothiazoline- 6-sulfonic acid) and reducing power assay for CEE were determined as 0.037 mg/mL, 0.68 mg/mL and 0.44 mg/mL, respectively. Besides eugenol, High Performance Liquid Chromatography (HPLC) analyses identified the presence of kaempferol, gallic acid and catechin in CEE. As a conclusion, we concluded that there was a possible synergistic effect between eugenol and the others active compounds especially kaempferol which led to the observed bioactivities in CEE.